1985
DOI: 10.1017/s0021859600059529
|View full text |Cite
|
Sign up to set email alerts
|

Wool growth of pregnant and lactating Merino ewes

Abstract: The wool production of pregnant, lactating and non-pregnant, non-lactating (dry) Merino ewes eating one of three diets: chaffed oaten hay (OH), chaffed lucerne hay (LH), and a 50/50 (w/w) mixture of OH and LH, was determined. Measurements were made for 2 months prior to mating, during pregnancy and for 3 months after lambing, and for the dry ewes over the same period.Production of clean wool (Y, g/day) by dry ewes was linearly related to digestible organic matter intake (X, g/day): Y = 00301X-3-34, r = 0-97. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The differences in wool growth between the pregnancy categories were consistent across allowances, as found by Oddy (1985). Oddy calculated the reduction in the wool growth of single and twin-bearing ewes from the wool growth/feed intake regression for dry ewes and found that this did not change significantly over a wide range of feed intake and wool growth values.…”
Section: Liveweight Gainsupporting
confidence: 61%
“…The differences in wool growth between the pregnancy categories were consistent across allowances, as found by Oddy (1985). Oddy calculated the reduction in the wool growth of single and twin-bearing ewes from the wool growth/feed intake regression for dry ewes and found that this did not change significantly over a wide range of feed intake and wool growth values.…”
Section: Liveweight Gainsupporting
confidence: 61%
“…As a result, while dry matter intake increases during pregnancy and lactation, the efficiency with which dry matter is turned into wool decreases (SCA, 1990). With the same nutrition, ewes that lamb in a given year produce approximately 0.4-0.5 kg less CFW than dry ewes, with the deficit being higher for twin bearing ewes (Oddy, 1985;Waters et al, 2000;Lee et al, 2009). FD tends to decrease along with reduced wool growth (Lee and Atkins, 1995) although Lee et al (2009) found that it varied little between flocks of ewes which differed in reproduction rate by as much as 1 lamb/ewe/year.…”
Section: General Effects Of Pregnancy and Lactationmentioning
confidence: 99%
“…The adverse influence of the stress of reproduction on fibre traits is well-documented (Turner et al, 1968;Corbett, 1979;Oddy, 1985;Charlick & Arnold, 1990). The clean wool production of ewes shorn prior to lambing was increased (P < 0.05) compared to contemporaries shorn prior to joining.…”
Section: Discussionmentioning
confidence: 95%